SYNCHRONIZATION OF OVULATION USING CIDR FOR OVARIAN CYSTS IN CATTLE - HONPARKHE, M; GHUMAN, S P S; SINGH, JAGIR (The Indian Journal of Animal Reproduction, 2011)
The objective of this study was to document ovarian and endocrine responses associated with the treatmentof ovarian cysts in dairy cattle, using controlled internal drug release (CIDR) regimens. Eight cattle of group-A wereadministered GnRH analogue (20μg Buserelin) on day 0, PGF2a (500μg Cloprostenol) on day 7 and 2nd GnRH(20μg Buserelin) on day 9. In addition, CIDR (1 .38g progesterone) was inserted on day 0 till day 7. Eight cows ofgroup-B received PGF 2« (500μg Cloprostenol) on day 0, concurrent with the intravaginal placement of CIDR for 15days followed by GnRH analogue (20μg Buserelin) on day 17. Cattle were inseminated (Al) at 72 hrs after CIDRremoval. In group-A, following day 0 treatment, complete luteinization of cystic structure as well as of large follicleoccurred in all cattle (p
Keywords: Cattle; CIDR; Conception rate; GnRH; Ovarian cyst